Sarcoidosis following SARS‐CoV‐2 infection: Cause or consequence?. Issue 6 (27th April 2022) - Palones, Esther; Pajares, Virginia; López, Laura; Castillo, Diego; Torrego, Alfons
Abstract: The COVID‐19 pandemic has been a worldwide medical challenge. Despite rapid advancements, many questions regarding SARS‐CoV‐2 interaction with other pathologies and long‐term consequences remained unanswered. Sarcoidosis is a multi‐systemic granulomatous disease that develops in genetically predisposed individuals following their exposure to an environmental trigger. We present the case of a patient who was diagnosed with sarcoidosis following a SARS‐CoV‐2 infection. Abstract : Sarcoidosis is a multi‐systemic granulomatous disease that develops in genetically predisposed individuals following their exposure to an environmental trigger. We present the case of a patient who was diagnosed with sarcoidosis following a SARS‐CoV‐2 infection.